O12.3 Evaluation of a Community-Based HIV Preventive Intervention For Female Sex Workers in Rural Areas of Karnataka State, South India. (13th July 2013) - Washington, R G; Nath, A; Jawalkar, P; Isac, S; Moses, S
Abstract : Background: To examine changes in behavioural outcomes among rural female sex workers (FSWs) involved in a community-based HIV preventive intervention in south India. Methods: 14, 284 rural FSWs from 1, 253 villages that were selected through a process of rapid rural mapping were reached by community workers (called link workers) and FSW peer educators over a period of three years between 2009 and 2012. A community-based model for delivering outreach, medical and referral services was developed and employed. Socio-demographic profiles of the FSWs and programme outputs were captured using an individualised computerised management information system (CMIS). Changes in behaviour were assessed in an anonymised fashion using two rounds of polling booth surveys (PBS) conducted in 2009 and 2012. Results: 91% of FSWs were above the age of 25, and 85% had been involved in sex work for two or more years. During the three-year period, 95% of the mapped FSWs were reached at least once, 80.3% received condoms as per need, and 71% received health services for sexually transmitted infections. In 2012, 45% reported having been tested for HIV infection, at least once in the previous six months. The two rounds of PBS showed significant differences in behavioural outcomes. Condom use increased from 60% to 72%, and condom breakage reduced from 30. 2% to 8.4%. Utilization of HIV counselling and testing services increased from 64% to 92.4%, and the proportion of FSWs testing HIV positive declined from 2.3% to 0.17%. Conclusions: This community-based model for delivering HIV prevention programmes and services among widely dispersed female sex workers in rural areas was effective. Community-based health workers provided the vital link between marginalised communities in need of services and the formal health system. This model for rural outreach and HIV care could also be applied to many other health problems.